Respuesta :
we are asked to prove tan(θ / 2) = sin θ / (1 + cos θ). In this case, tan θ is equal to sin θ / cos θ. we can apply this to the equality. sin θ is equal to square root of (1-cos θ)/2 while cos θ is equal to square root of (1 + cos θ)/2.
Hence, when we replace cos θ with square root of (1-cos θ)/2, we can prove already.
Hence, when we replace cos θ with square root of (1-cos θ)/2, we can prove already.
Answer:
Step-by-step explanation:
We have to prove the identity[tex]tan(\frac{\Theta }{2})=\frac{sin\Theta}{1+cos\Theta }[/tex]
We will take right hand side of the identity
[tex]\frac{sin\Theta}{1+cos\Theta}=\frac{2sin(\frac{\Theta }{2})cos(\frac{\Theta }{2})}{1+[2cos^{2}(\frac{\Theta }{2})-1]}[/tex]
[tex]=\frac{2sin(\frac{\Theta }{2})cos(\frac{\Theta }{2})}{2cos^{2}(\frac{\Theta }{2})}[/tex][tex]=\frac{sin(\frac{\Theta }{2})}{cos(\frac{\Theta }{2})}[/tex]
[tex]=tan(\frac{\Theta }{2})[/tex] [ Tan θ will be positive since θ lies in 1st quadrant ]
= L. H. S.
Hence proved.